THE ALTERNATIVE SANCTIONS SYSTEMS IN SERBIA AND THE NETHERLANDS: COMPARATIVE ANALYSIS WITH EXAMPLES FROM CASE LAW - Olga Tešović; Lieneke de Klerk (Revija za kriminologiju i krivično pravo)
Alternative sanctions are a deviation from the traditional system of imprisonment and their advantage certainly lies in a more humane and less repressive treatment of convicted persons. Alternative sanctions need to be present in the criminal sanctions system of every country in order to make this system more effective, primarily having in mind the goals of special prevention. This paper aims to present the alternative sanctions systems in Serbia and the Netherlands, respectively, with reference to case law examples, as well as to perform a comparative analysis of the two systems and indicate their advantages and disadvantages, as well as methods of their improvement.